Survey of Pain Curricula for Healthcare Professionals in Norway. (March 2014) - Leegaard, Marit; Valeberg, Berit T.; Haugstad, Gro Killi; Utne, Inger
Aim: The objective of the present study is to describe the content of pain curricula and the time designated to pain education for different healthcare professionals in Norway. Background: Clinicians encounter the challenge of unrelieved pain frequently, and evidence indicates they lack sufficient knowledge and skills to adequately assess and manage pain. Effective pain management is multifactorial and different health professionals must collaborate to meet the patients' needs. Methods: The Pain Education Survey was sent to 47 program leaders in Norwegian Health Faculties. The questionnaire consists of six close-ended questions concerning how the faculties organize their pain curricula and eight questions regarding the specific content. Findings: A total of 25 respondents across all healthcare educational institutions in Norway filled in the questionnaire, and the response rate varied between disciplines. Non-mandatory pain education was only reported by physiotherapy and nursing education. The most frequently taught area in all disciplines was non-pharmacological methods. The least taught areas were quality indicators and pain guidelines. Conclusions: This study describes great differences in how Norwegian healthcare educational institutions organize their pain curricula. It is worrying that only half of the respondents could identify clearly which areas were taught about pain.